Get to Know Public Relations Practitioners and Their Way Before and During Covid-19 - Abdul Rauf Ridzuan; Siti Sarah Jamil; Syed Haikal Arid Syed Johan; Noraini Adilla Mohd Diah; Fatin Nur Alaina Mohd Sobri (USIM Press, 2024)
VOL. 1 NO. 1 (2021): (Page 81-93)